The communication role of extracellular vesicles in the osteoarthritis microenvironment - Chen, Pu; Zeng, Lingfeng; Wang, Ting; He, Jianbo; Xiong, Shuai; Chen, Gang; Wang, Qingfu; Chen, Haiyun; Xie, Jiewei (Frontiers in Immunology, 2025)
Osteoarthritis (OA) is the most common degenerative joint disease worldwide, characterized by synovial inflammation, cartilage loss, and reactive hyperplasia of subchondral bone, affecting the quality of life of hundreds of millions of people. However, the molecular mechanisms underlying the occurrence and progression of OA remain unclear, and there is no therapy can substantially interrupt or reverse the destructive process of OA. More insight into the pathogenesis of OA may result in innovative therapeutics. The OA microenvironment plays a pivotal role in the development and progression of OA, which encompasses chondrocytes, adipocytes, synovial fibroblasts, endothelial cells, and immune cells. Extracellular vesicles (EVs) have emerged as a novel form of intercellular communication, mediating the transfer of a range of bioactive molecules to create a specific microenvironment. Recent studies have reported that the cargos of EVs play a crucial role in the pathogenesis of OA, including noncoding RNAs (ncRNAs), proteins, and lipids. This review systematically analyzes and summarizes the biological characteristics and functionalities of EVs derived from diverse cellular sources, especially how EVs mediate communication between different cells in the OA microenvironment, with a view to providing new insights into the pathogenesis of OA.